2022
DOI: 10.1186/s41983-022-00482-w
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Attention Deficit Hyperactivity Disorder and epilepsy: a literature review

Abstract: Background Attention Deficit Hyperactivity Disorder (ADHD) is a prevalent neurological disorder. ADHD has been linked to epilepsy. Main body ADHD was found to be present in 30–40% of epileptic children. Researchers have developed numerous theories to explain how and why ADHD and epilepsy coexist. Whether ADHD and epilepsy symptoms are caused by co-occurring psychiatric disorders or by the temporary effects of epileptic discharges or by antiepilepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…Additionally, this study did not analyze the relationship between epileptiform changes, epileptic syndromes, and specific ADHD symptoms, which could be relevant considering that several studies have been published on this subject. For example, some authors believe that epileptiform changes located over the rolandic, temporal, or frontal leads of the EEG, regions, are closely related to ADHD symptoms (Ahmed et al, 2022; Parisi et al, 2010). Frequent absence seizures may have a decrease in attention span.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study did not analyze the relationship between epileptiform changes, epileptic syndromes, and specific ADHD symptoms, which could be relevant considering that several studies have been published on this subject. For example, some authors believe that epileptiform changes located over the rolandic, temporal, or frontal leads of the EEG, regions, are closely related to ADHD symptoms (Ahmed et al, 2022; Parisi et al, 2010). Frequent absence seizures may have a decrease in attention span.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al reported that epilepsy symptoms are caused by co-occurring psychiatric disorders and antiepileptic medicines are essential for diagnosis and treatment of this epileptic disorder. 39 Tanaka et al…”
Section: Discussionmentioning
confidence: 99%
“…Finally, children with ADHD+ASD had an additive pattern of both entities. Ahmed et al (2022) raise the interest of the electroencephalographic studies in patients with epilepsy and ADHD since, although both conditions can appear comorbidly -and ADHD is more prevalent among patients with epilepsy-, sometimes the core symptoms of ADHD in epileptic patients could be exclusively related to the epilepsy itself or to its treatment.…”
Section: Support For Differentiation Of Comorbiditiesmentioning
confidence: 99%